2014
DOI: 10.1016/j.soard.2013.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic reversal of Roux-en-Y gastric bypass: Technique and utility for treatment of endocrine complications

Abstract: Background The anatomical and physiological changes with Roux-en-Y gastric bypass (RYGB) may lead to uncommon but occasionally difficult to treat complications such as hyperinsulinemic hypoglycemia with neuroglycopenia and recalcitrant hypocalcemia associated to hypoparathyroidism. Medical management of these complications is challenging. Laparoscopic reversal of RYGB anatomy with restoration of pyloric function and duodenal continuity is a potential treatment. Objective To present the indications, surgical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(56 citation statements)
references
References 35 publications
3
48
0
5
Order By: Relevance
“…Campos demonstrated that reversal of RYGB to normal anatomy or modified sleeve gastrectomy in hyperinsulinemic hypoglycemia and/or recalcitrant hypocalcemia associated with hypoparathyroidism was safe and successful in a minimally invasive fashion [28,29]. Similar to our study, a feeding gastrostomy tube was inserted into the excluded stomach and improvement of symptoms was documented prior to reversal of RYGB to normal anatomy.…”
Section: Discussionsupporting
confidence: 77%
“…Campos demonstrated that reversal of RYGB to normal anatomy or modified sleeve gastrectomy in hyperinsulinemic hypoglycemia and/or recalcitrant hypocalcemia associated with hypoparathyroidism was safe and successful in a minimally invasive fashion [28,29]. Similar to our study, a feeding gastrostomy tube was inserted into the excluded stomach and improvement of symptoms was documented prior to reversal of RYGB to normal anatomy.…”
Section: Discussionsupporting
confidence: 77%
“…A much larger number of patients might suffer from vague symptoms and are therefore not being diagnosed with post-gastric bypass hypoglycemia. Subsequently, they are not offered adequate treatment, which might consist of dietary modifications [18,28], acarbose [29][30][31], octreotide [15,32], verapamil [33] or diazoxide [34] as drug therapy or surgical interventions such as secondary bypass banding [35,36], bypass reversal [37,38] or pancreatic resection [24][25][26][27]39]. In our study, CGM provided better detection rates for post-RYGB hypoglycemia compared with MMT.…”
Section: Discussionmentioning
confidence: 68%
“…Also in 2013, Vilallonga et al described 10 patients who underwent conversion to SG and 10 who underwent reversal to normal anatomy for a variety of indications (7) . Finally, Campos et al described 3 patients converted to SG and 2 reversed to normal anatomy, all with resolution of hyperinsulinemic hypoglycemia or severe hypocalcemia following inadvertent parathyroidectomy after RYGB (9) .…”
Section: Discussionmentioning
confidence: 99%
“…Such a procedure has been described for correction of retrograde intussusception (5) , weight regain (6,7) , intractable dumping syndrome (8) , cachexia (7) , severe neuroglycopenia (7,9) , and hypocalcemia following inadvertent parathyroidectomy (9) . Currently, there are 5 series in the literature describing a total of 27 patients who have undergone conversion from RYGB to SG.…”
Section: Introductionmentioning
confidence: 99%